SEASONAL SURFACE GEOSTROPHIC CURRENT IN ARAFURA-TIMOR WATERS - Fachry Ramadyan; Ivonne M. Radjawane (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
Research on the seasonal geostrophic surface current during 2002-2011 in Arafura-Timor waters was conducted using satellite altimetry data. Those data were absolute dynamic topography and absolute geostrophic velocity data taken from Archiving Validation and Interpretation of Satellite Oceanographic data (AVISO). The dynamics of geostrophic surface current varied in every monsoon due to the difference in absolute dynamic topography. During northwest (NW) season, the absolut dynamic topography in Arafura Sea was higher than in Timor Sea by an average difference of 0.1–0.2 m and the geostrophic surface current moved from Arafura Sea toward Timor Sea. During southeast (SE) season, the absolute dynamic topography in Arafura Sea lower than Timor Sea with an average difference of 0.03-0.04 m. In this season, upwelling occurs in Banda Sea and sea surface water in this region becomes lower and the current moved from Arafura Sea to Banda Sea. The absolut dynamic topography difference between Arafura Sea and Timor Sea in NW and SE monsoons was 0.05–0.06 m and so the geostrophic surface current moved from Arafura Sea toward Timor Sea. In Timor Sea, the current moved southwest towards the Indian Ocean. In NW and SE Monsoons the the velocity of surface geostrophic current in Timor Sea (0,3 m/sec) was higher compare in Arafura Sea (0.2 m/sec) due to the configuration of island surround the Timor Sea and its topography. Keywords: Geostrophic surface current, altimetrysatellite, Arafura-Timor Sea